Performan Reproduksi Sapi PO pada Dataran Rendah dan Dataran Tinggi di Provinsi Jambi - Iskandar, Iskandar (Fakultas Peternakan Universitas Jambi, 2011)
The research was conducted to evaluate the reproductive performance of PO cattle on lowland and highland in Jambi Province. Sekernan Regency (lowland) and Kayu Aro Regency (highland) were purposively chosen as a sample of two different area. Data were analyzed using Z-test. The number of cattle reared was relatively similar between Sekernan Regency (1.98 heads) and Kayu Aro Regency (2.02 heads). Reproductive performance of PO cattle was significantly different (P<0.01) between two areas on age of puberty (Kayu Aro vs Sekernan : 672,76 d vs 823.44 d), age of first mating ( 694.11 d vs 847.89 d). service period (114.00 d vs 162.45 d). Service per conception in Kayu Aro and Sekernan was 1.3 and 1.5 respectively. In conclusion, there were differences on reproductive performance of PO cattle between lowland and highland areas in Jambi Province.